EFFECTS OF COMBINED EXERCISE TRAINING IN MORPHOLOGICAL AND NEUROMUSCULAR PARAMETERS OF ELDERLY WOMEN (Fiep Bulletin - online, 2012)
The purpose of this study was to investigate the effects of a combined physical training program on body composition and muscle strength in elderly women. This study was characterized as experimental. The study included 61 women, aged between 60 and 80 years, 40 of them belonging to the training group (TG) in Physical Activity Program for Seniors in Guarapuava-Pr, and 23 in the control group.(CG). All participants performed a pre-training evaluation, after which they were subjected to exercise training combined with machines, free weights and aerobics. After 24 weeks they were re-evaluated. The results showed a significant increase in TG in muscle strength of upper limbs (18.5 ± 5.8 to 21.3 ± 4.1), and maintaining muscle strength of lower limbs (14.5 ± 5.1 to 14 , 3 ±3.7). There was also improvement in the the CG, but not significant to upper limb strength (18.4 ± 2.9 to 19.4 ± 3.2) and lower limbs (14.9 ± 4 ,1 to 15.0 ± 4.1), achieving reductions in both combined training program with aerobic activity and anaerobic benefits and provides several positive changes In older women, contributing and helping with a better quality of life, and reflecting on health maintenance and provision of more performing everyday tasks.
Keywords: Physical training; muscle strength and elderly women